2022
DOI: 10.3389/fphys.2022.837482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiac Telerehabilitation During COVID-19 on Cardiorespiratory Capacities in Patients With Coronary Artery Disease

Abstract: BackgroundThe COVID-19 pandemic led to the closure of most cardiac therapy centers. One of the solutions was to adapt the existing cardiac rehabilitation (CR) program in an institute to a remote approach offered by home-based telerehabilitation. The aim of this study was to measure the cardiorespiratory effects of telerehabilitation compared to conventional center-based CR.MethodsPatients were assigned to two 3-week CR programs: telerehabilitation and conventional center-based CR. The telerehabilitation group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Our results are comparable to other studies that showed equal benefits of home-based telerehabilitation in comparison with center-based rehabilitation (Maddison et al, 2019;Batalik et al, 2020;Fanget et al, 2022). Furthermore, people with prolonged post-COVID symptoms have often demonstrated reduced exercise capacity (VO 2 values ≤85% of predicted values).…”
Section: Discussionsupporting
confidence: 84%
“…Our results are comparable to other studies that showed equal benefits of home-based telerehabilitation in comparison with center-based rehabilitation (Maddison et al, 2019;Batalik et al, 2020;Fanget et al, 2022). Furthermore, people with prolonged post-COVID symptoms have often demonstrated reduced exercise capacity (VO 2 values ≤85% of predicted values).…”
Section: Discussionsupporting
confidence: 84%
“…Our study reported that the most common barrier affecting the referral of HF patients for CR from the perspectives of nurses was the lack of CR centers. There is only one CR center in the Kingdom of Saudi Arabia specifically for patients with cardiovascular diseases, including HF [ 16 , 27 ]. This scenario shows and highlights the urgent need or requirement to create and develop new CR programs that meet global standards and can help existing HF patients across the country.…”
Section: Discussionmentioning
confidence: 99%
“…The Modified Borg Scale [ 32 ] will be used to assess the dyspnea symptoms and physical health. The participants will be required to walk for 6 min in a corridor with the distance of 30 m and to fill in the questionnaire or to describe verbally of the degree of dyspnea.…”
Section: Methodsmentioning
confidence: 99%